Mengatasi Buta Huruf Al-Qur’an pada Orang Dewasa di Desa Dagang Kerawan dengan Menggunakan Metode Qirati - Deddy Irawan; Ahmad Fadhlan; Siti Nur Annisa; Afiq Azizah; Sakholid Nasution (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The number of Muslim communities who are still illiterate in reading the Qur'an is a problem for a long time. This problem is not only found in children but also targets adults. This is what happened to the people of Dagang Kerawan village. Therefore, a program to overcome Al-Qur'an illiteracy was carried out in the Dagang Kerawan village community. This article aims to describe the program to overcome illiteracy in the Koran at the adult level in Dagang Kerawan village using the Qiroati learning method. This research uses a qualitative approach with the type of case study research; describe the phenomena as they are in the research location. Collecting data using observation, interviews, and documentation. The data analysis uses data reduction techniques, and drawing conclusions. The results of this study indicate that the use of the Qiroati learning method in overcoming illiteracy of the Qur'an in adults in Dagang Kerawan village is going quite well. Planning is poured in the form of a KKN program plan. Every adult is required to be able to meet the minimum completeness criteria (KKM) of learning. This program can help adults in Dagang Kerawan village be able to recognize letters and be able to read the Qur'an well even though there are many obstacles.